Applicability and quality assessment of the set of equipment in the project "Polygon for physical activity of school-aged children" in primary schools without gymnasia - Krtalić, Slaven (Array, 2020)
In 2015, 120 main primary schools in Croatia did not have a school gymnasium, and could not carry through the full-time compulsory Physical Education (PE) class. To ensure regular physical exercise to all children and help teachers, the Croatian Institute of Public Health has implemented the project “Polygon for Physical Activity of School-Aged Children”. This paper aims to present the usability and functionality assessment of the multipurpose kinesiology equipment set used in the Project in the primary schools without gymnasia based on the teachers’ experience and appraisals in three independent assessment waves. Results show that after receiving the set the teachers perceived they had better conditions for teaching Physical Education class and managed to fulfil PE curriculum goals and tasks. Students’ motivation for physical education class also improved in some areas, as well as teachers’ satisfaction with the conditions for and school investments in PE class. Most of the teachers perceived that the multipurpose kinesiology equipment set had the potential to improve the quality of PE class and to be used in other classes as well. According to the obtained data it could be assumed that this multipurpose kinesiology equipment set is a positive innovation in the teaching process and presents a strong potential for alleviating the spatial and material problems teachers in schools without gymnasia are experiencing in their work.